(untitled) (Journal of Parents and Teachers, 2013)
This article reflects whether it is adequate or not the fact that children can see contents that produce fear. The author defends that fear doesn’t need to be bad itself, but we should analyze if it is appropriate depending on the age. The article makes reference to several films.